2017
DOI: 10.1002/jee.20174
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Thinking in Prekindergarten Children: A Systematic Literature Review

Abstract: Background Children begin foundational learning in early childhood that sets the stage for later learning and academic success. Research regarding engineering in early childhood is limited yet growing.Purpose Because interest in engineering in early childhood is growing, this article reviews research regarding interactions, materials, and activities that promote prekindergarten children's engineering thinking, and in turn how this engineering thinking is related to developmental outcomes. Scope/MethodThe initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…STEM is an educational practice to integrate science, mathematics, engineering, and technology within formal and informal context and it provides practical opportunities for the child to make sense of the world holistically (Lantz, 2009;Marcus, Haden & Uttal, 2017;Marcus, Haden & Uttal, 2018). Moreover, the most important benefit of STEM activities for children, including engineering design, is to improve or support children's science and mathematics skills and social-emotional development (Katehi, et al 2009b;Lippard et al, 2017). In recent years, thus, early STEM education has been a remarkable subject for researchers in Turkey and they have obtained various findings from their studies.…”
Section: This Studymentioning
confidence: 99%
“…STEM is an educational practice to integrate science, mathematics, engineering, and technology within formal and informal context and it provides practical opportunities for the child to make sense of the world holistically (Lantz, 2009;Marcus, Haden & Uttal, 2017;Marcus, Haden & Uttal, 2018). Moreover, the most important benefit of STEM activities for children, including engineering design, is to improve or support children's science and mathematics skills and social-emotional development (Katehi, et al 2009b;Lippard et al, 2017). In recent years, thus, early STEM education has been a remarkable subject for researchers in Turkey and they have obtained various findings from their studies.…”
Section: This Studymentioning
confidence: 99%
“…Although the engineering design process model has been used extensively in secondary and postsecondary engineering education, its application in early childhood contexts remains limited. Lippard et al (2017) identified and reviewed only 27 studies related to engineering thinking in preschool. The majority of these studies measured a construct theoretically related to engineering, without directly measuring engineering (e.g., associations of spatial ability and mathematics with block building; Verdine et al, 2014;Wolfgang et al, 2001) or studied engineering thinking in less-traditional play contexts such as robotics, often with school-age children (e.g., Bers, 2007).…”
Section: Engineering Play Frameworkmentioning
confidence: 99%
“…The majority of these studies measured a construct theoretically related to engineering, without directly measuring engineering (e.g., associations of spatial ability and mathematics with block building; Verdine et al, 2014;Wolfgang et al, 2001) or studied engineering thinking in less-traditional play contexts such as robotics, often with school-age children (e.g., Bers, 2007). Moreover, many of these studies discussed implications of preschool-age engineering skills using theory and related developmental constructs as proxies (Lippard et al, 2017). Clearly, there is a need to directly measure engineering thinking and behavior among preschool-age children.…”
Section: Engineering Play Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of thinking is "goal-oriented thinking that addresses problems and decisions within given constraints by drawing on available resources, both material resources and human capital." 1 Thinking like an engineer, making, and tinkering are all part of engineering design-based learning.…”
mentioning
confidence: 99%